2012
DOI: 10.1111/hir.12001
|View full text |Cite
|
Sign up to set email alerts
|

Information needs of public health practitioners: a review of the literature

Abstract: Objective: To review published literature covering the information needs of public health practitioners and papers highlighting gaps and potential solutions in order to summarise what is already known about this population and models tested to support them. Methods: The search strategy included bibliographic databases LISTA, LISA, PubMed and Web of Knowledge. The results of this literature review were used to create two tables displaying published literature. Findings: The literature highlighted that some rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…This review replicates the findings of previous studies that found access, funding, and time to be major barriers to using evidence-based information [15, 16]. Additionally, several studies in this review highlighted external factors like political climate, organizational culture, and funding mandates [10, 30, 39, 45, 47, 50].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This review replicates the findings of previous studies that found access, funding, and time to be major barriers to using evidence-based information [15, 16]. Additionally, several studies in this review highlighted external factors like political climate, organizational culture, and funding mandates [10, 30, 39, 45, 47, 50].…”
Section: Discussionsupporting
confidence: 86%
“…Although literature reviews on this topic exist [15, 16], none have employed systematic search strategies or critical appraisal. The main aim of this study is to assess information needs of public health workers based on a review of the literature using a systematic search strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Public health professionals need timely access to current data from reliable, high quality sources [9, 55, 58, 59, 61, 62]. Furthermore, public health professionals need synthesized and collated data on relevant information such as best practices, effective prevention strategies or interventions, and evidence-based research, to name a few [9, 55, 59, 61, 63]. Public health professionals gather information from colleagues, literature and health departments [55, 57, 58, 62, 64].…”
Section: Resultsmentioning
confidence: 99%
“…Public health professionals gather information from colleagues, literature and health departments [55, 57, 58, 62, 64]. However, multiple studies suggested that public health professionals are still often unaware of available information resources, and emphasized collaboration to improve search outcomes [56, 60, 63, 65]. Additional challenges associated with meeting information needs include external barriers (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Barr-Walker, 2017;Ford & Korjonen, 2012), health care providers (e.g., Younger, 2010) or of academic researchers (e.g., Haglund & Olsson, 2008;Niu et al 2010 Figure 1.…”
Section: Out Of Scopementioning
confidence: 99%